Evaluasi Sistem Informasi Penggajian Pada PT XYZ - Hari Setiabudi Husni; Purwoko Purwoko; Antonius Antonius (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The purpose of this study was to identify problems and weaknesses in the payroll information system, providing recommendations to reduce the risk of existing problems and produce audit reports for companies. Research method used is through literature study, interviews and observation. Audit method used is the method of auditing around the computer. Analysis was performed by analyzing the findings of problems, risks, and recommendations on the findings of the problem. After doing research, we conclude that there are still some weaknesses in management control and application control. But companies should be more focus on the weaknesses inherent limitations in controlling the application and control the output. Based on these findings, suggested that the company to rectify existing weaknesses and enhance control over payroll information system.